Regional diets targeting gut microbial dynamics to support prolonged healthspan - Low, Dorrain Yanwen; Hejndorf, S.; Rachel, Thomas T. *; Poppema, Sibrandes *; Pettersson, S. (Frontiers Media, 2021)
In the last 150 years, we have seen a significant increase in average life expectancy, associated with a shift from infectious to non-communicable diseases. The rising incidence of these diseases, for which age is often the largest risk factor, highlights the need for contemporary societies to improve healthy ageing for their growing silver generations. As ageing is an inevitable, non-reversing and highly individualised process, we need to better understand how non-genetic factors like diet choices and commensal gut microbes can modulate the biology of ageing. In this review, we discuss how geographical and ethnic variations influence habitual dietary patterns, nutrient structure, and gut microbial profiles with potential impact on the human healthspan. Several gut microbial genera have been associated with healthy elderly populations but are highly variable across populations. It seems unlikely that a universal pro-longevity gut microbiome exists. Rather, the optimal microbiome appears to be conditional on the microbial functionality acting on regional- and ethnicity-specific trends driven by cultural food context. We also highlight dietary and microbial factors that have been observed to elicit individual and clustered biological responses. Finally, we identify next generation avenues to modify otherwise fixed host functions and the individual ageing trajectory by manipulating the malleable gut microbiome with regionally adapted, personalised food intervention regimens targeted at prolonging human healthspan.